PERSEPSI MASYARAKAT DESA PISAK TERHADAP PENGELOLAAN MODEL DESA KONSERVASI - Wahyuningsih, Ade; Zainal, Sofyan; Fahrizal, . (JURNAL HUTAN LESTARI, 2017)
Disturbance to protected areas Nyiut Mountain Nature Reserve from the village who lives close to the nature reserve, one of which is the village Pisak. Almost all conservation areas in Indonesia are in a strong pattern of interaction with the people living around them. Where the people living around the conservation area still rely on life in the forest. One of the activities undertaken by BKSDA as a form of activities in forest conservation is to make the Model Village Conservation Village as one of the first step in the community empowerment that is located around the conservation area of Gunung Nyiut Nature Reserve. The method used was a survey method with interview-assisted questionnaire. Determination of the number of respondents using Slovin formula and its determition by purposive sampling. Data analysis using Chi Square formula. Perception of community pisak village towards Management of Village Conservation Models in Nyiut Mountain Nature Reserve tend to be different. Perception of community on the management of conservation village ,odels are likely to be positive. It is proven that as many as 39 respondents ( 44,32 %) has a positive perception on the management of the Village Conservation Model conducted in Pisak village, in addition to greatly helping the community burden to get clean water, also assist in the preservation of the area they occupy today. There is a significant correlation between knowledge and cosmopolitan factors with community perception factor, but there is no correlation between age factor and perception of Pisak villagers towards the management of Village Conservation Model conducted in Pisak village.Keywords: Model Desa Konservasi, Perception, Pisak Village.